House dust mite allergen Der f 1 induces IL-8 in human basophilic cells via ROS-ERK and p38 signal pathways. Issue 2 (October 2015) - Yi, Myung-hee; Kim, Hyoung-Pyo; Jeong, Kyoung Yong; Kim, Chung-Ryul; Kim, Tae Yun; Yong, Tai-Soon
Highlights: Der f 1 induces IL-8 on KU812 without recognition of allergens by IgE antibodies. Der f 1 increases AP-1 and phosphorylation of NF-κB p65 in KU812 cells. Proteolytic activity of Der f 1 activates the ERK and p38 signaling pathways. Der f 1-induced IL-8 expression is partially regulated by ROS. Abstract: Der f 1, a major house dust mite allergen and member of the papain-like cysteine protease family, can provoke immune responses with its proteolytic activity. To understand the role of Der f 1 in inflammatory immune responses, we studied the mechanism of the regulation of interleukin (IL)-8 expressions in human basophilic cell KU812 by proteolytically active recombinant Der f 1. Not only production of IL-8 mRNA was induced but also the DNA binding activity of activator protein-1 (AP-1) and phosphorylation of NF-κB p65 were increased in Der f 1-treated KU812. Furthermore, Der f 1 induction of IL-8 expression was sensitive to pharmacological inhibition of ERK and p38 mitogen activated protein kinase (MAPK) pathways. Der f 1 also activated ERK and p38 MAPK phosphorylation and rapidly induced reactive oxygen species (ROS) production. The antioxidant N-acetyl-cysteine (NAC) inhibited phosphorylation of ERK, but not p38, suggesting that secretion of IL-8 in KU812 cells treated with Der f 1 is dependent on ROS, ERK MAPK and p38 MAPK. We describe the mechanism of Der f 1-induced IL-8 secretion from human basophilic cells, which are thought to be important for allergic inflammation independent of IgE antibodies. These findings improve our understanding of the inflammatory immune response in human basophils to protease allergens.